Anthropogenic influences and climate changes in Lake Hazar (eastern Turkey) during the Late Holocene - Biltekin, Demet; Eris, Kursad Kadir; Bulut, Selda (Pergamon-Elsevier Science Ltd, 2021)
Palaeoecological reconstruction was carried out at Lake Hazar in eastern Turkey from 3.2 cal ka BP to -510 cal years BP. To evaluate vegetation and climate changes, palynological and grain size analysis were performed by comparing geochemical data, magnetic susceptibility (MS), and Total Organic Carbon (TOC). A lake level reconstruction has been done by palynological data, indicating local environmental changes at Lake Hazar. The first lake level rise was recorded between 3.2 and 2.9 cal ka BP, showing higher river discharge due to the wetter climate. This is also evidenced by higher values in Ca/Ti and TOC values, in coarser grain size and the abundance of trees (mainly deciduous Quercus), while non-arboreal plants (NAP) decrease in the environs of Lake Hazar. A sharp drop follows this in lake level between 2.9 and 2.2 cal ka BP, evidenced by a higher the Sr/Ca ratio and fine-grained sediment (<35 ?m), whereas the Ca/Ti ratio and TOC value decline. This longer drought was followed by the more extended period of humidity between 2.2 cal ka BP and -650 yrs BP, consistent with a higher MS value, and the Ca/Ti ratio and TOC. The results identified a number of aridity events between 1.6 and 1.3 cal ka BP, at 1.1 cal ka BP, and at cal. -900 yrs BP, evidenced by a high Sr/Ca ratio. A cultivation period starts to appear at 1.6 cal ka BP with Juglans (walnut) during the Sassanid dynasty in the region. Aridity event at 1.1 cal ka BP, corresponding to Medieval Warming, was characterized by dry climate and lake level drop. Simultaneously, the cultivation of walnut, olive, and Pistachio declined. The existence of Plantago lanceolata, Rumex, Sanguisorba minor-type, Scabiosa and Caryophyllaceae indicate farming and animal husbandry activities during the Late Holocene.
Keywords: Pollen analysis; Anthropogenic indicators; Lake level fluctuations; Lake Hazar; Late Holocene